2016
DOI: 10.7127/rbai.v10n500465
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiração Horária X Diária Utilizando Penmanmonteith Para O Polo De Desenvolvimento Petrolinape/Juazeiro-Ba

Abstract: RESUMOO conhecimento da evapotranspiração é de fundamental importância para a estimativa da necessidade de irrigação. Entre os diversos métodos existentes para a realização do cálculo, o método de Penman-Monteith é considerado como o que mais se ajusta a diversas localidades, podendo calcular a evapotranspiração de referência tanto utilizando dados diários quanto horários. O objetivo deste trabalho foi avaliar as estimativas de evapotranspiração de referência (ETo) pelo método de Penman-Monteith em períodos di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…These changes in Vv values may be associated with the observations made by [25] in the same region, which, in a study of the hourly ETo calculation, verified the interference of the wind speed during short periods of time. Thus, there are different ways of responding to the different rates of variation of Vv for CWSs when compared to AWSs.…”
Section: Resultssupporting
confidence: 64%
“…These changes in Vv values may be associated with the observations made by [25] in the same region, which, in a study of the hourly ETo calculation, verified the interference of the wind speed during short periods of time. Thus, there are different ways of responding to the different rates of variation of Vv for CWSs when compared to AWSs.…”
Section: Resultssupporting
confidence: 64%
“…The average seasonal trend for ETo 24h and ETo d in Paraná State were also similar and close, with the Cfa "d" index equal to 0.97 for spring and summer; and Cfb "d" index equal to 0.99 in the spring and 0.98 in the summer. Lopes & Leal (2016) associating ETo d vs ETo 24h for semiarid climate obtained an agreement "d" index ranging from 0.98 to 0.99. In the present study, lower "d" indexes were observed in the autumn and winter periods for Cfa climate.…”
Section: Eto D Trend and Association Between Eto D And Eto 24h Througmentioning
confidence: 93%
“…Dhungel et al (2019) studying evapotranspiration in a BSh (dry semi-arid) climate obtained mean ETo d values in a lysimeter ranging from 0 to 12 mm day −1 . Lopes & Leal (2016) observed that the ETo d and ETo 24h methodologies have different results when taking months or seasons into consideration. When working with a reduced number of data, such as a few months, there is no possibility to analyze ETo considering the changes in meteorological variables throughout the year.…”
Section: Eto D Trend and Association Between Eto D And Eto 24h Througmentioning
confidence: 99%
See 1 more Smart Citation